OXCT1 Enhances Gemcitabine Resistance Through NF-κB Pathway in Pancreatic Ductal Adenocarcinoma - Ding, Jinsheng; Li, Hui; Liu, Yang; Xie, Yongjie; Yu, Jie; Sun, Huizhi; Xiao, Di; Zhou, Yizhang; Bao, Li; Wang, Hongwei; Gao, Chuntao (Frontiers in Oncology, 2021)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is a type of malignant tumor with a five-year survival rate of less than 10%. Gemcitabine (GEM) is the most commonly used drug for PDAC chemotherapy. However, a vast majority of patients with PDAC develop resistance after GEM treatment. Methods We screened for GEM resistance genes through bioinformatics analysis. We used immunohistochemistry to analyze 3-oxoacid CoA-transferase 1 (OXCT1) expression in PDAC tissues. The survival data were analyzed using the Kaplan–Meier curve. The expression levels of the genes related to OXCT1 and the NF-κB signaling pathway were quantified using real‑time quantitative PCR and western blot analyses. We performed flow cytometry to detect the apoptosis rate. Colony formation assay was performed to measure the cell proliferation levels. The cytotoxicity assays of cells were conducted using RTCA. The downstream pathway of OXCT1 was identified via the Gene Set Enrichment Analysis. Tumor growth response to GEM in vivo was also determined in mouse models. Results Bioinformatics analysis revealed that OXCT1 is the key gene leading to GEM resistance. Patients with high OXCT1 expression exhibited short relapse-free survival under GEM treatment. OXCT1 overexpression in PDAC cell lines exerted inhibitory effect on apoptosis after GEM treatment. However, the down-regulation of OXCT1 showed the opposite effect. Blocking the NF-κB signaling pathway also reduced GEM resistance of PDAC cells. Tumor growth inhibition induced by GEM in vivo reduced after OXCT1 overexpression. Moreover, the effect of OXCT1 on GEM refractoriness in PDAC cell lines was reversed through using an NF-κB inhibitor. Conclusion OXCT1 promoted GEM resistance in PDAC via the NF-κB signaling pathway both in vivo and in vitro. Our results suggest that OXCT1 could be used as a potential therapeutic target for patients with PDAC.